Eulepida mbala, a new species from Zambia (Coleoptera: Scarabaeidae: Melolonthinae) - Sehnal, Richard (Zootaxa, 2018)
The genus Eulepida Kolbe, 1894 (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) was established to accommodate 10 Afrotropical species, seven new and three previously placed in Lepidiota Kirby, 1828, Proagosternus Blanchard, 1851, and Tricholepis Hampson, 1891. Lacroix (2010) designated Leucopholis lepidota Klug, 1855 as the type species of the genus Eulepida. Currently the genus contains 20 species divided into three groups based on morphological characters (Lacroix 2010, 2013): species group I includes Eulepida lepidota (Klug, 1855), E. minor Moser, 1913, E. nitidicollis Kolbe, 1894, E. nyassica Kolbe, 1894, E. sinuatifrons (Fairmaire, 1887), and E. zambiensis Lacroix, 2010; species group II includes E. anatina Brenske, 1896, E. tschindeana Péringuey, 1904, and E. werneri Lacroix, 2010; and species group III includes E. baumanni Kolbe, 1894, E. flavovestita Moser, 1913, E. gracilipes Kolbe, 1894, E. kameruna (Frey, 1972), E. kenyensis Lacroix, 2010, E. mamboiae Brenske, 1896, E. manowensis Moser, 1913, E. mashona Arrow, 1902, E. montana Kolbe, 1894, E. reichei (Thomson, 1858), and E. savagei (Hope, 1842). Examination of material recently collected in Zambia revealed an undescribed species belonging to species group II (sensu Lacroix 2010). This group is defined by the combination of the following characters: protibia bidentate; antennal club distinctly longer than antennal shaft; pygidium narrow, longer than wide, with a pronounced elongate terminal invagination; and parameres symmetrical, long, evenly curved in ventral aspect (Lacroix 2010). The purpose of this paper is to describe one new species, to add new geographic records for some Eulepida species of group II, and to update the key for this group. New faunistic records are reported for Eulepida tschindeana and Eulepida werneri from Zimbabwe.
Keywords: Animals; Orthoptera; brouci; zvířata; Zimbabwe; Zambie; Coleoptera; Coleoptera, Scarabaeidae, Melolonthinae; Montana; Zambia